"Inbreeding and its Relevance to Early and Pre-reproductive Mortality Rates in Iran, an Ecological Study" - M Saadat; H Mohabbatkar (Tehran University of Medical Sciences, 2003)
Consanguinity has been a long-standing social habit among Iranians. The effect of consanguinity on early death (stillbirth plus infant death) and pre-reproductive mortality (death before age 15 years) was studied in an ecological study in 10 provinces of Iran (including, Boosheher, Chaharmahal-O-Bakhtiari, East Azarbaijan, Ilam, Fars, Kashan, Kerman, Kermanshah, Markazi, Semnan, and Yazd). The rates of early death and pre-reproductive mortality of the study populations were derived from the data from 20th March 2000 to 19th March 2001. Statistical analysis showed that there were significant correlation coefficients between mean of inbreeding coefficients of provinces and either early death (r=+0.611, t=2.32, df=9, P=0.046) or pre-reproductive mortality (r=+0.627, t=2.41, df=9, P=0.039) rates. When consider the frequency of consanguinity in terms of individual city of the study provinces, statistical analysis showed that early death (r=+0.324, t=3.18, df =86, P=0.002) was significantly correlated with the mean of inbreeding coefficients of populations.